Tinjauan Hukum Islam terhadap Rekaman Suara sebagai Alat Bukti Tindak Pidana di Peradilan: Islamic Legal Review of Audio Recordings as Evidence of Criminal Acts in Court Proceedings - Muhammad Taufan Djafri; Asri, Asri; Ihsan Muhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to identify the types of evidence that can be used in proving criminal acts in court according to Islamic law, as well as to analyze the position and validity of audio recordings as evidence of criminal acts in court from the perspective of Islamic law. This is a library research study employing normative and empirical juridical approaches. Data collection was conducted through documentary studies of relevant literature sources, and data analysis employed deductive techniques. The research findings indicate that in Islamic law, the types of evidence that can be used to prove criminal acts are syahādah (testimony), yamīn (oath), iqrār (confession), and qarīnah (sign or indication). The review of Islamic law regarding audio recordings as evidence of criminal acts states that audio recordings can be accepted if they meet the requirements of being accessible, audible, accountable, integrity-guaranteed, and capable of elucidating the circumstances. Audio recordings can be analogized with the qarīnah (indication) evidence in Islamic law. This research contributes to the discipline of Islamic criminal law by examining the use of audio recordings as evidence of criminal acts from the perspective of Islamic law, enriching the repertoire of Islamic criminal law in responding to technological advancements and evolving modes of crime in the modern era.